The Revival of Civil Society
XV, 255 p.
Keywords: What is meant by the concept of civil society? Why do some equate it with liberal democracy, while others think it simply a guise for a market economy? Who benefits from globalization and who loses out? Can civil society prosper in an era of globalization? Can global civil society restrain some of the negative consequences of economic globalization? Through a series of unique case studies and theoretical inquiries, this volume provides a set of concrete answers to questions such as these.